2012
DOI: 10.2977/prims/60
|View full text |Cite
|
Sign up to set email alerts
|

Super Duality and Homology of Unitarizable Modules of Lie Algebras

Abstract: The u-homology formulas for unitarizable modules at negative levels over classical Lie algebras of infinite rank of types gl(n), sp(2n) and so(2n) are obtained. As a consequence, we recover the Enright's formulas for three Hermitian symmetric pairs of classical types (SU (p, q), SU (p) × SU (q)), (Sp(2n), U (n)) and (SO * (2n), U (n)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Corollary 5.8 provides an alternative description involving an infinite Weyl group. Ngau Lam has informed us that both forms of the formula are equivalent[19].…”
mentioning
confidence: 98%
“…Corollary 5.8 provides an alternative description involving an infinite Weyl group. Ngau Lam has informed us that both forms of the formula are equivalent[19].…”
mentioning
confidence: 98%
“…in Proposition 3.1 is a monomorphism of Lie superalgebras with * -structures, and we have shown that the map ϕ given in Lemma 2.3 is an isomorphism of Lie superalgebras with * -structures from (g given in [EHW,Sections 8 and 9] (see also [HLT,Theorem 2.5]).…”
Section: Unitarizable Modules Overmentioning
confidence: 83%
“…The Weyl group W x n of g x n is defined to be the subgroup of Aut((h x n ) * ) generated by all σ α (cf. [HLT,Section 2.3]).…”
Section: Lie Algebras Of Infinite and Finite Ranksmentioning
confidence: 99%